2023
DOI: 10.4103/ijnm.ijnm_125_22
|View full text |Cite
|
Sign up to set email alerts
|

Tibial stress fracture and “Shin Splint” syndrome in the same patient diagnosed on 99mTC-Methylene diphosphonate bone scintigraphy and single-photon emission/computed tomography

Abstract: We present a case of an 18-year-old male athlete who presented with complaints of right lower leg pain for 10 days following intense exercise. The most likely diagnosis was a possible tibial stress fracture or a ''shin splint'' syndrome. The radiograph did not reveal any significant abnormality in the form of any fracture or a cortical break. We performed planar bone scintigraphy including single-photon emission computed tomography (CT)/CT that revealed the presence of the two concomitant pathologies in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…Fluorine-18 (18F) is one of the main emitters of these particles in nuclear medicine. [11] Glucose labeled with 18F (18F-FDG) forms a complex that is taken up by cells with increased glucose metabolism. [12] After entering the cytoplasm through glucose transporters, this complex is metabolized into FDG-6-phosphate.…”
Section: Pet/ctmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorine-18 (18F) is one of the main emitters of these particles in nuclear medicine. [11] Glucose labeled with 18F (18F-FDG) forms a complex that is taken up by cells with increased glucose metabolism. [12] After entering the cytoplasm through glucose transporters, this complex is metabolized into FDG-6-phosphate.…”
Section: Pet/ctmentioning
confidence: 99%
“…They found that SPECT/CT imaging demonstrated high diagnostic accuracy for detecting prosthesis loosening in these cases. [11]…”
Section: Pet/ctmentioning
confidence: 99%
See 1 more Smart Citation